DESAFIOS PARA EL PERU: APEC Y TLC - Mauricio Pachas, Pablo (2006)
About APEC few people know its importance, but it has been discussed about Tried Free Commerce (TLC) with United States. In this article the importance of Asia in the world economy is indicated, a brief characterization of the main Asian markets is carried out (Chinese, Japan, South Korea and Taiwan), and is analyzed the possibilities of Peru to be constituted in a strategic platform for the South American commerce with the Asia in the framework of the APEC. Also, it is discussed the expectations to open new markets with the main commercial blocks through Tried Free Commerce.